2023
DOI: 10.1038/s41598-023-31448-4
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative neutrophil-to-lymphocyte ratio correlates with PD-L1 expression in immune cells of patients with malignant pleural mesothelioma and predicts prognosis

Abstract: We assessed the prognostic value of five complex inflammatory and nutritional parameters, namely neutrophil-to-lymphocyte ratio (NLR), prognostic nutritional index (PNI), C-reactive protein-to-NLR ratio (C/NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) using data from patients with malignant pleural mesothelioma (MPM) undergoing extrapleural pneumonectomy (EPP). Moreover, the correlation between these five parameters and programmed cell death protein 1 ligand-1 (PD-L1) express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
1
1
Order By: Relevance
“…This finding mirrors the existing literature in which neutrophils to lymphocytes ratio is associated with worse outcomes in PM. 20,21 Interestingly, in our study histology did not prove to be either prognostic or predictive at univariate analysis. This might be explained by the low number of non-epithelioid histology patients enrolled and further investigation regarding the activity of nivolumab in non-epithelioid mesothelioma is warranted.…”
Section: Discussioncontrasting
confidence: 78%
“…This finding mirrors the existing literature in which neutrophils to lymphocytes ratio is associated with worse outcomes in PM. 20,21 Interestingly, in our study histology did not prove to be either prognostic or predictive at univariate analysis. This might be explained by the low number of non-epithelioid histology patients enrolled and further investigation regarding the activity of nivolumab in non-epithelioid mesothelioma is warranted.…”
Section: Discussioncontrasting
confidence: 78%
“…In a retrospective study, it was found that C-NLR could be used as an important indicator to predict the poor prognosis of patients with malignant pleural mesothelioma undergoing extrapleural pneumonectomy, which has a certain clinical significance. 42 There are also studies that define C-NLR as CRP×neutrophil-to-lymphocyte ratio to predict poor prognosis in patients with heart failure and pancreatic cancer after surgery. 43 , 44 However, studies on the combination of CRP and LMR are relatively lacking, and C-NLR and C-LMR are rarely used in the field of cerebrovascular diseases.…”
Section: Discussionmentioning
confidence: 99%